229k views
3 votes
The picture reeeeeeeeeeeeeeeeeeeeeeeeee

The picture reeeeeeeeeeeeeeeeeeeeeeeeee-example-1

2 Answers

2 votes

Answer:

D. 3x - 3

Explanation:

To find (f-g)(x) you have to subtract each fuction

(f-g)(x) = f(x) - g(x)

(f-g)(x) = 5x -2 - (2x+1)

(f-g)(x) = 5x -2 -2x -1

(f-g)(x) = 3x -3

User Amon
by
4.7k points
6 votes

Answer:

3x - 3

Explanation:

this can be written as

f(x) - g(x)

so since we know what f(x) and g (x) are equal to :

5x - 2 - 2x - 1 = 3x -3

User Salem
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.